The new interpretation of generalized operation functional for optimal control of smallsized unmanned aerial vehicles - Лысенко, А. И.; Тачинина, Е. Н.; Назаренко, Е. В. (Problems of Informatization and Control, 2015)
This paper proposes the new interpretation of generalized operation functional for optimal control ofsmall-sized unmanned aerial vehicles